2019
DOI: 10.28916/lsmb.3.5.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal bioactive compounds to functional foods from geochemical signatures marine biomasses: sea cucumbers, macroalgae and crown of thorns biomasses

Abstract: Recognition of health benefits associated with consumption of marine derived biomasses is one of the most promising developments in human nutrition and disease-prevention research. This endeavor for bioactives and functional ingredients discovery from marine sources is "experience driven," as such the search for therapeutically useful synthetic drugs, and functional components is like "looking for a needle in a haystack," thus a daunting task. Zoonotic infection, adulteration, global warming and religious beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Seafood, such as bivalve shellfish, is a delicacy consumed all over the world. Meanwhile, they may also serve as a rich source of health-beneficial ingredients including proteins, peptides, essential amino acids, omega-3 long-chain polyunsaturated fatty acids, minerals and vitamins [2][3][4]. Many studies have demonstrated that the striped mussel (Mytilus edulis) contains a high percentage of protein (60-65% of dry weight) and essential amino acids (35-45% of total amino acids) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Seafood, such as bivalve shellfish, is a delicacy consumed all over the world. Meanwhile, they may also serve as a rich source of health-beneficial ingredients including proteins, peptides, essential amino acids, omega-3 long-chain polyunsaturated fatty acids, minerals and vitamins [2][3][4]. Many studies have demonstrated that the striped mussel (Mytilus edulis) contains a high percentage of protein (60-65% of dry weight) and essential amino acids (35-45% of total amino acids) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted that A. planci possess a steadily therapeutic potential (Ghazali et al, 2017;Lee et al, 2014;Mutee et al, 2012;Tan et al, 2013). Crown of thorns starfish are a prolific source of bioactive compounds (Ghazali et al, 2019). They are widely distributed in the world's ocean including Fiji's territories with clear traces of historical coral impacts (Dumas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%